2019
DOI: 10.1142/s0218271820400131
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational lensing by a magnetized compact object in the presence of plasma

Abstract: We study the gravitational lensing in the weak field approximation assuming the presence of a plasma and of a magnetic field around a compact gravitational source. The external magnetic field causes the split of the image, as the counterpart of the Zeeman effect. The magnetic field affects the magnification of images, creating additional components. We also study the time delay of an electromagnetic signal due to the geometry and the gravitational field around the source. We show that the time delay strongly d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…In comparison with the deflection angle computed by Turimov et al [68], they found the deflection angle of a light ray passing near a magnetized static compact object surrounded by weak inhomogeneous plasma while we have evaluated the deflection angle by using GBT in a weak gravitational lensing for spherically symmetric spacetime incorporating magnetic field and correction parameter β.…”
Section: Deflection Angle With Impact Parameter Bmentioning
confidence: 88%
See 1 more Smart Citation
“…In comparison with the deflection angle computed by Turimov et al [68], they found the deflection angle of a light ray passing near a magnetized static compact object surrounded by weak inhomogeneous plasma while we have evaluated the deflection angle by using GBT in a weak gravitational lensing for spherically symmetric spacetime incorporating magnetic field and correction parameter β.…”
Section: Deflection Angle With Impact Parameter Bmentioning
confidence: 88%
“…He also discussed the influence of the magnetic charge on the black hole gravitational lensing. Recently, Turimov et al [68] have considered the magnetic field around a gravitational source and illustrated that the split of the Einstein ring, as the counterpart of the Zeeman effect. When the cyclotron frequency approaches to the plasma frequency, the size and the form of the ring change because of the presence of a resonance state.…”
Section: Deflection Angle With Impact Parameter Bmentioning
confidence: 99%
“…Now, let us assume that we solve these equations of motion by setting the new parameterp 0 to take the same numerical value that p 0 (which must be a constant throughout the world-lines of the light rays because of (22)). In that situation, we see that with the exception of the first of these expressions, all of them agree with equations (14)- (17), and in particular the spatial orbit will be exactly the same.…”
Section: Spatial Orbits Associated To a Gordon-like Metricmentioning
confidence: 99%
“…Nevertheless there exists in actuality some radio-telescope projects that work in the frequency bandwidth in which these effects could be observable [42][43][44][45][46]. Motivated by that, a proliferation of works dealing with the influence of plasma media on the trajectory of light rays in a external gravitational field associated to compact bodies have resurged [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%